Petrology of the gabbro and sheeted basaltic intrusives at North Cape, New Zealand - Hopper, D.J.; Smith, I.E.M. (Royal Society Of New Zealand, 1996)
The North Cape massif consists of a semiconformable sequence of serpentinite, gabbro, sheeted sill and dike units, and pillow lavas. Although structurally disrupted, they can be interpreted in terms of an idealised ophiolite sequence and represent the most complete sequence in the Northland Ophiolite. Their age is considered to be Late Cretaceous - Paleocene on the basis of microfossils in associated sediments. Early Miocene K-Ar ages from igneous rocks are thought to reflect the time of emplacement as a thrust sheet of oceanic crust and upper mantle. The gabbros are divided into a lower unit characterised by well-developed cumulate layering and an upper unit which is massive; the sheeted sills and dikes are quartz-diorite and microgabbro interleaved with minor pillow lava. Two phases of alteration are observed, a pervasive low-grade greenschist metamorphism attributed to sea-water interaction after formation as oceanic crust, and an overprinting zeolitic alteration which is possibly post-emplacement Their tholeiitic nature as well as overlapping geochemical compositions suggest that the gabbros and sheeted dikes and sills represent different components of a single magmatic system related by simple fractionation processes. Several lines of evidence suggest that the magmas that formed the North Cape gabbro and sheeted intrusives have subduction-related chemical characteristics. In the gabbro, calcic plagioclase (An86-92) and depleted Zr and Y abundances, and in the sheeted intrusives depleted high field strength element abundances relative to typical MORB, is indicative of a subduction signature. The presence of subduction-related characteristics within the Northland Ophiolite suggests that it may have originated at a back-arc basin rather than a major ocean ridge spreading centre. An open access copy of this article is available from the publishers website.